JNFS 2022
DOI: 10.54216/jnfs.020102
|View full text |Cite
|
Sign up to set email alerts
|

A Short Note On The Kernel Subgroup Of Intuitionistic Fuzzy Groups

Abstract: This paper defines the concept of kernel subgroup of an intuitionistic fuzzy group. Also, it proves that this kernel is a group in the ordinary algebraic meaning as a direct application of the concept of kernel in fuzzy and anti-fuzzy groups. Also, we derive some properties of intuitionistic fuzzy groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Garg et al, [14] discussed two more measures for IF sets. Jia and Wang [15] evaluated Choquet aggregation operators using integralbased IF information, and Bal et al, [16], developed the theory of subgroup in relation to IF sets. Panda and Nagwani [17] established infection preparation created on well-organized software for IF evidence, and Gu et al, [18] observed the risk calculation model for IF material.…”
Section: Introductionmentioning
confidence: 99%
“…Garg et al, [14] discussed two more measures for IF sets. Jia and Wang [15] evaluated Choquet aggregation operators using integralbased IF information, and Bal et al, [16], developed the theory of subgroup in relation to IF sets. Panda and Nagwani [17] established infection preparation created on well-organized software for IF evidence, and Gu et al, [18] observed the risk calculation model for IF material.…”
Section: Introductionmentioning
confidence: 99%
“…For more development on , we refer to Refs. [ [28] , [29] , [30] , [31] , [32] ]. In addition, the ideas of an intuitionistic fuzzy ring [ 33 ], an intuitionistic fuzzy ideal [ 34 ], an intuitionistic fuzzy normed ring [ 35 ], an intuitionistic fuzzy soft ring [ 36 ], and an intuitionistic fuzzy normal subring [ 37 ] were proposed.…”
Section: Introductionmentioning
confidence: 99%
“…Tarsuslu et al [ 24 ] generalized the action of a group on a set to intuitionistic fuzzy action. Bal et al [ 25 ] investigated the kernel subgroup of intuitionistic fuzzy subgroups.…”
Section: Introductionmentioning
confidence: 99%